Penggunaan Gaya Bahasa Sindiran dalam Konten Channel Youtube Animasi Tekotok Tinjauan Pragmatik - Ega Bagas Setyangga; Nurchalistiani Budiana; Muhamad Toha (Departement of Mathematics Education, 2023)
Language is an utterance to be conveyed and packaged in the form of expression and has a function as a communication tool in certain situations in various activities. The style of satire has a figure of speech which is divided into five figures of speech, sarcasm, cynicism, anti-racism, irony. Tekotok is an animation created by Bilal and Beto, which was designed in December 2020. The storyline for tekotok is very concise. However, it is in line with everyday life, and contains satire, knowledge, light jokes, comparisons, anxiety, and criticism from many parties, to the personal emotionality of the animators. The video presents unique and critical information about the government. Researchers used qualitative type research through descriptive methods. Qualitative Research is research that is commonly used in humanities research, social sciences, and other types of research. Qualitative research is describing in the form of content analysis, namely research that leads to content studies that have a direction and purpose to interpret the values that exist in research objects through verbal descriptions. The research design used in the following research is descriptive qualitative research. Qualitative descriptive research is a type of research that aims to provide a general description of the social environment, the correlation events being tested. Qualitative research is a research method that examines a person's writing or speech and attitudes that can be studied. So, in conclusion, satirical language is the use of language style in the application of everyday life which has the aim of satirizing the object of conversation or someone. Researchers put forward an article about how the meaning of satire language is in one of the YouTube channels.